Excimer-ultraviolet-lamp-assisted selective etching of single-layer graphene and its application in edge-contact devices - Minjeong Shin; Jin Hong Kim; Jin-Yong Ko; Mohd Musaib Haidari; Dong Jin Jang; Kihyun Lee; Kwanpyo Kim; Hakseong Kim; Bae Ho Park; Jin Sik Choi (Nano Convergence, 2024)
Abstract Since the discovery of graphene and its remarkable properties, researchers have actively explored advanced graphene-patterning technologies. While the etching process is pivotal in shaping graphene channels, existing etching techniques have limitations such as low speed, high cost, residue contamination, and rough edges. Therefore, the development of facile and efficient etching methods is necessary. This study entailed the development of a novel technique for patterning graphene through dry etching, utilizing selective photochemical reactions precisely targeted at single-layer graphene (SLG) surfaces. This process is facilitated by an excimer ultraviolet lamp emitting light at a wavelength of 172 nm. The effectiveness of this technique in selectively removing SLG over large areas, leaving the few-layer graphene intact and clean, was confirmed by various spectroscopic analyses. Furthermore, we explored the application of this technique to device fabrication, revealing its potential to enhance the electrical properties of SLG-based devices. One-dimensional (1D) edge contacts fabricated using this method not only exhibited enhanced electrical transport characteristics compared to two-dimensional contact devices but also demonstrated enhanced efficiency in fabricating conventional 1D-contacted devices. This study addresses the demand for advanced technologies suitable for next-generation graphene devices, providing a promising and versatile graphene-patterning approach with broad applicability and high efficiency.